Mistakes as Shadow Capital in Human Ventures - Koumpis, Adamantios (International Journal of Advanced Corporate Learning (iJAC), 2014)
In the paper we present different approaches related to the conceptualisation of mistakes from the literature and situate them with a given methodological framework by Bourdieu. We also draw analogies with the notion of shadow capital and the relevance of applying reflexive learning as a practical means to deal with mistakes in the corporate environment.